Analyzing Bloom’s Taxonomy Levels in Students’ Speaking Activities in Teaching Modules of Kurikulum Merdeka - Yolanda Pratiwi; Irmayani; Khoirul Huda (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
Many senior high school students in Indonesia struggle with spoken English because their classroom curriculum lacks relevant and engaging speaking opportunities. This study aims to identify the cognitive levels represented in speaking activities and examine the extent to which they promote higher-order thinking skills (HOTS) in teaching modules based on the recent Kurikulum Merdeka. A qualitative directed content analysis by Hsieh & Shannon (2005) was employed, examining five teaching modules and Alur Tujuan Pembelajaran (ATP) from different senior high schools, obtained from the official Ministry of Education website. The findings showed that Applying (C3) occurred most frequently (63 occurrences; 44.68%), followed by Remembering (C1) with 24 occurrences (17.02%), and Understanding (C2) with 21 occurrences (14.89%). HOTS levels were less dominant, with Analyzing (C4) and Creating (C6) both appearing 15 times (10.64%), and Evaluating (C5) only 3 times (2.13%). This indicates a predominance of LOTS over HOTS in the modules. Analysis of speaking outputs revealed that high-output activities such as discussions and presentations (A4 and A5) occurred 49 times, while medium-output activities (A2 and A3) appeared 12 times, and low-output activities (A1) only once. These results suggest that although opportunities for communicative competence exist, speaking activities still lean toward tasks requiring lower cognitive engagement. It is concluded that while the Kurikulum Merdeka teaching modules integrate various Bloom’s Taxonomy levels, more emphasis is needed on HOTS to enhance critical thinking and creativity.